A highly sensitive epidermal sensor based on triple-bonded hydrogels for strain/pressure sensing. (December 2021) - Fan, Chonghui; Wang, Di; Huang, Jieyu; Ke, Huizhen; Wei, Qufu
Abstract: Hydrogels as a kind of soft material have received tremendous interests which are great promising candidate for wearable epidermal sensors to integrate prominent mechanical strength, high sensitivity and multiple detection mode. Herein, we proposed the synthesis strategy of a novel double network (DN) structure based on covalently crosslinked polyacrylic acid (PAA) network and ionic sodium alginate (SA) network to fabricate SAA (SA/PAA)/Al 3+ /MXene highly sensitive hydrogels for strain and pressure sensing. The strain sensors acquired a maximum gauge factor (GF) of 4.3 and fast response time of 210 ms, also displayed a good pressure sensitivity (0.075 kPa -1 ). Moreover, this epidermal sensor can monitor human motions by resistance or capacitance signals. We anticipated that this work can pave the way for designing wearable electric skins in the application of human motion monitoring and healthcare diagnosis. Graphical abstract: Image 1 Highlights: A novel epidermal sensor was synthesized with high sensitivity based on double network hydrogel. Covalent bond, ionic coordination bond and hydrogen bonding interactions formed triple-bonded structure. Thehydrogel sensors acquired a maximum gauge factor of 4.3, also displayed a good pressure sensitivity (0.075 kPa -1 ). Epidermal sensor could be attached to body parts to monitor joints motion and physiological signal.